(untitled) (Fiep Bulletin - online, 2013)
Background and Objective: To know the lifestyle of college students, especially risk behaviors related to health, it is important to support any decisions taken in the implementation of intervention programs within the university. The study aims to analyze the behavior of this population related to the perception of body weight. Methodology: The study population comprised students from UENP, where the 3304 volunteers who underwent the Youth Risk Behavior Survey questionnaire - College (YRBS-C) related to body weight. Results: The proportion of 54.8% of women reported their weight off than they wanted. A number of 24.5% of men judged to present just below or well below that expected body weight, of the total 51.7% of men reported ever tried to change your weight, among women, 51.3% indicated they have tried to maintain or reduce. To reduce or prevent weight gain, 69.1% ended up opting for low-calorie diets and physical activity by 47.7%. 77% of men opted for exercise. Still, 31.1% of women and 7.8% of men reported resorting to drugs, vomiting or laxatives to change your weight. Conclusion: The results obtained by women are related to psychological factors, for they are more concerned with their daily lives to the pursuit of the aesthetic ideal and male volunteers showed up with more nonchalance regarding body weight perception and self report when outside ideal weight seek a better way to combat this.